ALGUMAS CONSIDERAÇÕES SOBRE A FUNÇÃO DA CONSCIÊNCIA A PARTIR DAS PROPAGANDAS DA REFORMA DO ENSINO MÉDIO (Revista Contexto & Educação, 2021)
This article intends to bring some considerations about the function of the conscience from the advertisements propagated about the Reformation of the Secondary School. The two selected advertisements were transmitted during the period covered by Provisional Measure 746/2016. A troubled context during protests against the reform. In order to collaborate in this discussion, Vygotsky (1990, 1990a) discusses consciousness as a mechanism that mobilizes historical, social and duplicate experiences. From this process reflexive is that it arrives at the conditioned reflex and not only as a product of a stimulus. Raymond Williams (2016) with the discussion of television in its dual function: both as a technological apparatus and as a cultural form. It assists in the understanding of television within a space of disputes and not in a simple relation of cause and effect. The fact that young people reflect on the information conveyed and place them in a chain of reflexes and knowledge, the conscience acquires a primordial role in the formation of the human being. Activates the memory, the attention, the perception of the social surroundings for the formulation of concepts. And it does so from the historical reality, social and individual, therefore the unpredictability of human behavior.